IMPLEMENTASI STANDAR PROSES DALAM KURIKULUM 2013 DI SEKOLAH DASAR - Ndaru Mukti Oktaviani; Isnaini Wulandari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2019)
The curriculum 2013 is one of the policies of the Indonesian government in improving the quality of human resources through education that is adjusted to the needs of the community. Changes in the learning process in the curriculum 2013 have an impact on the readiness of teachers to implement it. Based on the results of the FGD conducted with elementary school teachers in the Kuningan region, it was stated that most of the teachers still had difficulties in implementing the learning process that was in accordance with the learning process of the 2013 curriculum. This statement should be explored further on what were the causes of teacher difficulties in applying the learning process in accordance with the curriculum 2013. Therefore it is necessary to conduct research on the implementation of standard processes in the curriculum 2013 in elementary schools. The research method used in this study is case study. The study was conducted at public elementary schools located in Kuningan Regency, namely SD Negeri Dukuhdalem, Japara District, SD Negeri 1 Manislor, Jalaksana District, and SD Negeri 1 Purwawinangun, Kuningan District. There are two types of research instruments used, namely observation sheets and interview guides. The results of the study note that the main obstacle in carrying out the syllabus in the curriculum 2013 is the lack of socialization in changing syllabus content, teachers have difficulty in making lesson plans, especially to include activities that are in accordance with the scientific approach, there is a gap between the material needed and the source of material in the book. provided, in the classroom management aspect the obstacle faced is the teacher's lack of readiness to follow changes in the learning process in the curriculum 2013, the teacher is still unable to carry out the demands of the learning process that is in accordance with the curriculum 2013 in the assessment process, most teachers complained about the complexity of the assessment process. The obstacle often faced by teachers was that the assessment instruments were still limited